Buckling analysis of laminated composite thin-walled I-beam under mechanical and thermal loads - Bui, Xuan-Bach; Nguyen, Anh-Cao; Nguyen, Ngoc-Duong; Do, Tien-Tho; Nguyen, Trung-Kien (Vietnam Journal of Mechanics, 2023)
Despite the extensive use of thin-walled structures, the studies on their behaviours when exposed to extreme thermal environment are relatively scarce. Therefore, this paper aims to present the buckling analysis of thin-walled composite I-beams under thermo-mechanical loads. The thermal effects are investigated for the case of studied beams undergoing a uniform temperature rise through their thickness. The theory is based on the first-order shear deformation thin-walled beam theory with linear variation of displacements in the wall thickness. The governing equations of motion are derived from Hamilton’s principle and are solved by series-type solutions with hybrid shape functions. Numerical results are presented to investigate the effects of fibre angle, material distribution, span-to-height’s ratio and shear deformation on the critical buckling load and temperature rise. These results for several cases are verified with available references to demonstrate the present beam model’s accuracy.